Scoping review protocol of central chronic medicines dispensing and distribution programme for widening access to medications in South Africa - Olanrewaju Oladimeji; Busisiwe Mrara; Olubunmi Margaret Ogbodu (BMJ Open)
Introduction The Central Chronic Medicines Dispensing and Distribution (CCMDD) programme, a differentiated alternative service delivery programme, initiated by the Department of Health, South Africa, allows clinically stable patients to receive chronic medication refills at the clinic-based or community-based pick-up points, offering stable patients suffering from non-communicable diseases an easy way to collect their medication. This facilitates the achievement of positive therapeutic outcomes and underscores the importance of this programme, which has resulted in decreased stigma concerns and optimising the workload for public health facilities and health workers. Therefore, this scoping review aims to explore and describe how the improved CCMDD programme has widened access to medications in South Africa in readiness for the implementation of the National Health Insurance.Methods and analysis This scoping review will be conducted using the Arksey and O’Malley framework and further refined by the Levac framework. The review will follow a six-step approach: (1) identifying the research question, (2) identifying relevant studies, (3) studying selection eligibility, (4) charting the data, (5) collating, summarising and reporting the results and (6) consultation. A comprehensive search strategy will be developed by searching studies published between 2014 and 2024 using the following electronic databases; PubMed, Web of Science and Google Scholar. Grey literature including conference abstracts and reports will also be searched. The Preferred Reporting Items for Systematic Reviews and the Meta-Analysis for Scoping Reviews (PRISMA-ScR) will be used as a guide for this scoping review protocol. Two independent reviewers will screen identified studies’ titles, abstracts and full texts. Discrepancies will be handled by consensus or consulting a third reviewer author. Data extraction will be conducted using a standardised form. The selection of studies for the review is anticipated to be completed within 10 weeks, from 15 March to 30 May 2025, with strict adherence to the guidelines of the PRISMA-ScR checklist.Ethics and dissemination This review, not requiring ethical approval, will inform policymakers, researchers and healthcare professionals to improve the deliverables of the CCMDD programme for all chronic conditions and ailments with a high prevalence in South Africa and identify any research gaps. We plan to disseminate our findings via a peer-reviewed journal, policy briefs, conference presentations and stakeholder engagement.